Spatial solitons in an electrically driven graphene multilayer medium - Muzzamal Iqbal Shaukat; Montasir Qasymeh; Hichem Eleuch (Scientific Reports, 2022)
Abstract We investigate the evolution of coupled optical solitons in a multilayer graphene medium. The considered graphene medium is subjected to microwave voltage biasing. The coupled two optical solitons emerge through the electrical (i.e., microwave voltage) perturbation of the effective permittivity of the graphene multilayer. We show that the coupled solitons are electrically adjustable by controlling the amplitude and frequency of the biasing microwave voltage. Importantly, this proposed regime of electrically controlled optical solitons offers a modality to generate entangled optical solitons and two-mode squeezed solitons. Furthermore, the hybrid interaction that includes both the driving microwave voltage and the optical solitons yields a platform to combine the two worlds of quantum photonics and quantum superconducting systems.